2015
DOI: 10.1016/j.soilbio.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of phosphatase activity and various bacterial phyla in the rhizosphere of Hordeum vulgare L. depending on P availability

Abstract: a b s t r a c tDespite the importance of the rhizosphere for nutrient turnover, little is known about the spatial patterns of organic phosphorus mineralization by plants and by microorganisms in the rhizosphere. Therefore, the distribution of acid and alkaline phosphatase activity and the abundance of bacteria belonging to various bacterial phyla were investigated in the rhizosphere of barley (Hordeum vulgare L.) as dependent on the availability of inorganic P. For this purpose, we conducted a greenhouse exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 61 publications
3
32
2
2
Order By: Relevance
“…They determined the PA in the rhizosphere of barley grown under low and adequate P soil conditions and observed a similarity of approximately 90% between alkaline and acid PA. In contrast to the experiment of Spohn et al (2015), we observed no distinct separation between roots and surrounding soil (Fig. S2) and also generally lower PA (Fig.…”
Section: Plant Growthcontrasting
confidence: 99%
See 3 more Smart Citations
“…They determined the PA in the rhizosphere of barley grown under low and adequate P soil conditions and observed a similarity of approximately 90% between alkaline and acid PA. In contrast to the experiment of Spohn et al (2015), we observed no distinct separation between roots and surrounding soil (Fig. S2) and also generally lower PA (Fig.…”
Section: Plant Growthcontrasting
confidence: 99%
“…These findings suggest increased P mineralization by microbial phosphatases produced by viable RU47. In general, zymography revealed similar activity levels for alkaline and acid PA, which is in accordance with Spohn et al (2015). They determined the PA in the rhizosphere of barley grown under low and adequate P soil conditions and observed a similarity of approximately 90% between alkaline and acid PA.…”
Section: Plant Growthsupporting
confidence: 77%
See 2 more Smart Citations
“…Soil zymography works for a large range of hydrolases Spohn and Kuzyakov, 2014]. The method has been especially useful for determining the distribution of enzyme activity in the rhizosphere Kuzyakov, 2013, 2014], and it has already been combined with other imaging methods, such as 14 C imaging and fluorescent in situ hybridisation [Spohn et al, 2015] to gain insights into rhizosphere processes (Fig. 2).…”
Section: Soil Zymographymentioning
confidence: 99%